The Role of Academic Emotions, Perception of the University Atmosphere and learning Behaviors in Predicting the Academic Enthusiasm of Farhangian University of East Azerbaijan - Ali Eghbali; Hossein Vahedi; Akbar Ebrahimi; Sorayya Eghlimi (مطالعات روانشناسی تربیتی)
The purpose of the present study was to determine the role of academic emotions, perceptions of the university atmosphere, and learning behaviors in predicting the academic enthusiasm among the teacher students of Farhangian University of East Azerbaijan. This research was of applied type and followed a descriptive-correlational method. The population included a total number of 3103 male and female student teachers in the academic year of 2020-2021. Out of which 342 student teachers were selected through Convenience sampling. Fredericks et al.'s (2004) academic enthusiasm, Pakran et al.'s (2005) academic excitement, Raf et al.'s (1997) educational environment, and McDermott et al.'s (1999) learning behaviors questionnaires were used to collect the data. The data were analyzed by means of Multiple Regression analysis of SPSS 22. The results showed that there was a direct positive relationship between positive academic emotions, perceptions of the university atmosphere, and learning behaviors, but the relationship was negative and reversely significance for academic emotions at p<0.001. The predictive power of positive academic emotions was higher than the other research variables. Therefore, it can be concluded that academic emotions, perceptions of university atmosphere, and learning behaviors play a role in explaining academic enthusiasm and some interventions on academic emotions, perceptions of the university atmosphere, and learning behaviors are necessary to improve academic enthusiasm.